Inflammatory response to the administration of mesenchymal stem cells in an equine experimental model: effect of autologous, and single and repeat doses of pooled allogeneic cells in healthy joints. Issue 1 (December 2016) - Ardanaz, N.; Vázquez, F.; Romero, A.; Remacha, A.; Barrachina, L.; Sanz, A.; Ranera, B.; Vitoria, A.; Albareda, J.; Prades, M.; Zaragoza, P.; Martín-Burriel, I.; et al.
Abstract Background Mesenchymal stem cells (MSCs) transplantation has become a promising therapeutic choice for musculoskeletal injuries. Joint-related disorders are highly prevalent in horses. Therefore, these animals are considered as suitable models for testing MSC-based therapies for these diseases. The aim of this study was to investigate the clinical and inflammatory responses to intra-articular single and repeat dose administration of autologous or of pooled allogeneic MSCs in healthy equine healthy joints. Six horses were intra-articularly injected with a single autologous dose of bone marrow derived MSCs (BM-MSCs) and two separate doses of allogeneic BM-MSCs pooled from several donors. All contralateral joints were injected with Lactated Ringer's Solution (LRS) as the control vehicle. Signs of synovitis and lameness were evaluated at days 0, 1, 2, 3, 5 and 10 after injection. Total protein (TP), white blood cell count (WBC) and neutrophil count (NC) in synovial fluid were also measured at the same time-points. Results A mild synovial effusion without associated lameness was observed after all BM-MSCs injections. The second allogeneic injection caused the lowest signs of synovitis. Local temperature slightly increased after all BM-MSCs treatments compared to the controls. TP, WBC and NC in synovial fluids also increased during days 1 to 5 after all BM-MSCs injections. Both, clinical and synovial parameters were progressively normalized and by day 10 post-inoculation appeared indistinguishable from controls. Conclusions Intra-articular administration of an allogeneic pool of BM-MSCs represents a safe therapeutic strategy to enhance MSCs availability. Importantly, the absence of hypersensitivity response to the second allogeneic BM-MSCs injection validates the use of repeat dose treatments to potentiate the therapeutic benefit of these cells. These results notably contribute to the development of stem cell based therapies for equine and human joint diseases.